PENENTUAN BERAT ISOTOP CESIUM DAN URANIUM DALAM PELAT ELEMEN BAKAR U3Si2/Al DENSITAS 4,8 gU/cm3 - Yanlinastut, Yanlinastut; Indaryati, Sutri; Boybul, Boybul; Supardjo, Supardjo; Ginting, Aslina Br. (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
DETERMINATION OF WEIGHT OF CESIUM AND URANIUM ISOTOPES IN IRRADIATED U3Si2/Al FUEL PLATE WITH 4.8 gU/cm3 DENSITY AND 40% BURN UP. The fuel plate of U3Si2/Al with a density of 4.8 gU/cm3 was irradiated in the RSG-GAS multipurpose reactor with 40% burn- up. During irradiation, the amount of isotopes produced by fission reaction, such as cesium, uranium and other isotopes can be used for burn-up calculation to determine the fuel performance. Physicochemical analysis was performed to determine the weight of cesium and uranium isotopes in the irradiated fuel. The irradiated plate of U3Si2/Al was cut at the middle section (duplo) with a weight of M-1 = 0.065 g and M-2 = 0.075 g and dissolved in HCl 6N and HNO3 6N. The resulted was pipetted at 100 µL and then added into each of 2 mL solvent of HNO3, H2SO4 and HCl 0.1N. The separation of cesium was then carried out with the addition 1000 mg of zeolite from Lampung. Cesium isotope obtained from the separation was bound with zeolite in the solid phase while uranium was in the liquid phase. Cesium isotopes in the solid phase and in the liquid phase were measured by a spectrometer- for their radioactivity for 10000 seconds. The measurement was indicated by spectra of 134Cs at 604.7 and 795.8keV energy and 137Cs at 661.7keV. Meanwhile, the separation of uranium in the liquid phase was carried out using anion exchange column method with the addition of Dowex resin. The results of the separation were indicated by some spectra of U isotopes at various energies, 238U at 4,1943 MeV, 235U at 4,397 MeV, 236U at 4,494 MeV and 234U at 4,777 MeV. Weight calculation from the measurement data shows that the weight of 137Cs in 0.056 g of the irradiated U3Si2/Al fuel samples in HNO3, H2SO4 and HCl solvent are 4.08E-05 g; 4.53E-05 g ,and 4.53E-05 g respectively, while 134Cs weight are 4,84E-08 g; 5,30E-08 g and 5,20E-08 g respectively. Meanwhile, 137Cs isotope weight in 0.075 g fuel plate of U3Si2/Al are obtained by 5.93E-07 g; 5.90-05 g, and 5.88E-05 g, while the isotope weight of 134Cs in HNO3, H2SO4 and HCl solvent are 5,23E-07 g; 5,29E-07g and 5,008E-07g respectively. The isotopes weight of 238U, 235U, 236U and 234U in 0.056 g of fuel plale are 6.45E-03 g; 2.57E-03 g; 2.42E-06 g; and 1.90E-05 g, and the weight in 0.075 g fuel plale are 7.41E-03 g; 2.40E-03 g; 2.91E-06 g; and 2.17E-05 g. The isotopes weight of 134Cs, 137Cs, 238U, 235U, 236U and 234U in 0.056 g and 0.075 irradiated U3Si2/Al fuel plate obtained were relatively similarly. Data of isotopes weight are then used as input data for burn up calculation.